2012
DOI: 10.1177/1090820x12456841
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Breast Implant Bacterial Contamination From Endogenous Breast Flora, Prevention With Nipple Shields, and Implications for Biofilm Formation

Abstract: The exposed nipple is a potential source of implant contamination during breast augmentation. An improved understanding of biofilms and related risk factors for CC can provide surgeons with insights for addressing this common complication. Meticulous hemostasis, use of nipple shields, and submuscular device placement may contribute to a lower incidence of CC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(35 citation statements)
references
References 53 publications
0
34
0
1
Order By: Relevance
“…The prospective cohort study design was nonrandomized and some previously hypothesized factors were not included in the analysis; examples include genetic disposition, nipple shields, and blood loss. 6,8,28,29 These factors were not included because they were unmeasured. In addition, to provide an overall risk profile, the analysis did not include separate models for early and late contractures.…”
Section: Limitationsmentioning
confidence: 99%
“…The prospective cohort study design was nonrandomized and some previously hypothesized factors were not included in the analysis; examples include genetic disposition, nipple shields, and blood loss. 6,8,28,29 These factors were not included because they were unmeasured. In addition, to provide an overall risk profile, the analysis did not include separate models for early and late contractures.…”
Section: Limitationsmentioning
confidence: 99%
“…7 Foreign body reaction is not yet fully understood and the pathogenesis of CC is still unclear, but it is believed to be mostly multifactorial, influenced by patient age, type of implant (shape, surface, and material), silicone leakage, individual susceptibility and propensity for hypertrophic scarring, surgical technique, surgical incision site, and occurrence of postoperative complications such as bleeding and hematoma formation. 1,4,7,[11][12][13][14] Recent evidence suggests that subclinical infection and the presence of a bacterial biofilm on the surface of the implant could be a likely major contributor to CC. [15][16][17] Interestingly, a high bacterial colonization rate of 61% to 66.7% has been detected in association with grade III and IV contractures, suggesting that bacterial stimuli may accelerate the process of inflammation and fibrosis.…”
mentioning
confidence: 99%
“…25,31 It has been suggested that subclinical infection could cause CC 25,31 and that the breast is a clean-contaminated surgical site where the most commonly identified organisms are of the Staphylococcus species, with Staphylococcus epidermidis present in 42% of positive cultures. 32,33 More recently, Wixtrom et al 33 showed that more than one-third of culture swabs from nipple and occlusive dressing taken after breast augmentation were positive for bacteria, suggesting that, without nipple shields, bacteria would likely be expressed onto the sterile surgical field.…”
Section: Discussionmentioning
confidence: 99%